Successful percutaneous extraction of malpositioned pacemaker lead in the left ventricle after proper dabigatran treatment. Issue 9 (7th April 2022) - Farouq, Maiwand; Borgquist, Rasmus; Brandt, Johan; Mörtsell, David; Wang, Lingwei
Abstract: Malpositioned pacemaker lead in the left ventricle (LV) is a rare procedural complication, which causes a special risk of thromboembolic events. Hence, prompt identification and early management of misplaced leads inside the LV is critical. Herein, we present a case of malpositioned pacemaker lead with transient ischemic attacks after the pacemaker implantation. The misplaced ventricular lead was discovered during regular echocardiography. Both leads were extracted percutaneously after dabigatran treatment. To our knowledge, this is the first report of uncomplicated percutaneous extraction of an inadvertently placed LV lead after dabigatran treatment. No neurologic events during a follow‐up of 4 years.